A wear-resistant self-lubricating copper-based composite material and preparation method thereof
By adding Ti3AlC2 and CaF2 to the aluminum bronze matrix, the coupling function is used to regulate the ratio, the adhesion and wear problem of aluminum bronze in oil-free and high-temperature conditions is solved, and the wear resistance and lubrication performance of the material is significantly improved.
Patent Information
- Application Number
- CN202410707455.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-06-03
AI Technical Summary
The adhesion and wear of aluminum bronze in oil-free and high-temperature conditions leads to a decrease in friction performance and service life. The existing technology has failed to effectively solve this problem after adding alloy elements.
By adding Ti3AlC2 and CaF2 to the aluminum bronze matrix simultaneously, the coupling function is used to regulate its ratio to reduce adhesion wear and abrasive wear, and reduce the friction coefficient and wear rate.
It significantly improves the wear resistance and lubricity of aluminum-bronze composite materials, is suitable for high-temperature oil-free working conditions, extends service life and reduces production costs.
Smart Images

Figure BDA0004873046500000071 
Figure BDA0004873046500000081 
Figure BDA0004873046500000082
Abstract
Description
Technical Field
[0001] The invention relates to a wear-resistant self-lubricating copper-based composite material and a preparation method thereof, belonging to the technical field of copper-based composite friction materials. Background Art
[0002] Aluminum bronze has good antioxidant properties, high strength, hardness and wear resistance, and is widely used in parts such as screws, nuts, copper sleeves, and sealing rings. Its superior corrosion resistance makes it often used to manufacture mechanical parts such as bearings, sleeves, gears, and turbines used in seawater environments. However, during the oil-free friction and wear process, the adhesive wear of aluminum bronze intensifies as the surface temperature increases, resulting in a rapid increase in the wear rate, and a significant decrease in the friction performance and service life of the parts. Therefore, the wear mechanism of aluminum bronze needs to be further optimized, and the friction performance needs to be further improved.
[0003] Chinese patent CN 105088004A improves the friction and wear properties of aluminum bronze by adding elements such as Cr and Si; Chinese patent CN112195361A improves the strength and wear resistance of aluminum bronze by adding elements such as Zn and Ti; Chinese patent CN104388749A reduces the friction coefficient and wear rate of aluminum bronze by adding elements such as Ce and B. However, the addition of the above alloying elements is mainly to strengthen the matrix through mechanisms such as grain refinement, and no strengthening phase and lubricating phase are added, so the reduction in friction coefficient and wear rate is small. Chinese patent CN107586989A obtains a product with excellent friction reduction and anti-wear properties by adding graphite, silver and lead as lubricating phases to copper alloys, but the cost of silver is high, lead will pollute the environment, and graphite has limited lubrication at high temperatures. In addition, the production cost of this material is high, and its ability to limit the adhesive wear mechanism is relatively weak. Chinese patent CN102703161A improves the wear resistance of the material by adding an appropriate amount of strengthening phase Ti3SiC2 to pure copper, but its matrix is pure copper, and its strength and hardness are much lower than copper alloys, making it difficult to use in heavy load and strong impact conditions. Chinese patent CN103184385A combines multiple M n+1 XA n The compound is added to the brake pad material as a reinforcing phase, but it lacks the coordination with the lubricating phase, resulting in a high friction coefficient and wear rate of the material. n+1 XA n The addition amount of the compound reaches 15-35%, and its high content easily leads to a decrease in the toughness and strength of the matrix. Therefore, if the matrix formula can be optimized, the reinforcing phase and lubricating phase can be added, and the preparation process can be improved to effectively limit its adhesive wear under oil-free and high-temperature conditions, the comprehensive performance and service life of the material will be significantly improved.
[0004] Studies have shown that adding alloying elements to aluminum bronze alloys can improve hardness and strength, but there are no reports on compounding Cr and La2O3 to improve the wear resistance of aluminum bronze alloys. At the same time, Ti3AlC2 has a high hardness, and its oxidation product at high temperature has a friction-reducing and anti-wear effect; CaF2 can form a stable lubricating film on the friction surface at high temperature, thereby reducing the friction coefficient. Some researchers have conducted research and applications on the friction performance of Ti3AlC2 and CaF2, but there is no research on adding Ti3AlC2 and CaF2 to aluminum bronze and precisely regulating their mutual coupling performance. Summary of the invention
[0005] In view of this, the present invention provides a wear-resistant self-lubricating copper-based composite material and a preparation method thereof, which optimizes the components of the copper-based composite material and the content of each component, that is, mainly adds Ti3AlC2 and CaF2 at the same time to produce a coupling effect, and adjusts their ratio to combine the weakening adhesive wear effect of Ti3AlC2 with the weakening abrasive wear effect of CaF2 to reduce the friction coefficient and wear rate, so that the wear resistance and lubrication performance of the composite material are significantly improved, meeting the requirements for use under oil-free conditions; and the preparation method of the composite material is simple, the raw materials are environmentally friendly, the cost is low, the economic benefit is high, and it has good application prospects in friction parts such as sliding bearings, bushings, and sliders.
[0006] The objectives of the present invention are achieved through the following technical solutions.
[0007] A wear-resistant self-lubricating copper-based composite material, with the total mass of raw materials for preparing the composite material being 100%, the raw materials have the following components and the mass percentage of each component: 78-92% of an aluminum bronze matrix phase, 3-10% of a Ti3AlC2 strengthening phase, and 5-12% of a CaF2 lubricating phase. The wear-resistant self-lubricating copper-based composite material can be obtained by sintering the raw materials.
[0008] Aluminum bronze is a copper-based alloy with aluminum as the main alloying element and containing other elements such as iron, manganese, and nickel. Preferably, the components of the aluminum bronze and the mass percentage of each component in the raw material for preparing the composite material are as follows: Cu 60-80%, Al 6.5-9.5%, Ni 1.5-2.5%, Fe 2.5-4%, Mn 0.5-1%, Cr 0.5-1%, and La2O3 0.5-1.0%. Preferably, the powder particle size of the above components except La2O3 is 200-300 mesh, and the particle size of La2O3 is 25-50μm.
[0009] Preferably, the Ti3AlC2 is prepared by sintering a mixed powder of Ti powder, Al powder and graphite powder under an inert gas protective atmosphere, wherein the sintering temperature is 1380-1420°C and the sintering holding time is 5-20min. More preferably, the temperature is increased to 1380-1420°C at a heating rate of 100-150°C / min.
[0010] Preferably, Ti powder, Al powder and graphite powder are mixed by high-energy ball milling under an inert gas protective atmosphere, wherein the ball-to-material ratio is 3:1-4:1, the ball milling speed is 250-350r / min, and the ball milling time is 8-10h. More preferably, in order to prevent the occurrence of ball sticking, can sticking and agglomeration during the ball milling process, anhydrous ethanol is added before the ball milling, and the ball milling process is stopped every 5-10min, and the ball milling is continued after stopping for 2-3min. Further preferably, the material of the ball milling jar and the ball milling beads is tungsten carbide.
[0011] Preferably, taking the total mass of raw materials for preparing Ti3AlC2 as 100%, the mass fractions of Ti powder, Al powder and graphite powder in the raw materials are 70-75%, 15-18% and 9-14% respectively.
[0012] Preferably, the particle sizes of Ti powder, Al powder and graphite powder are 25-50 μm; and the particle size of the prepared Ti3AlC2 is 25-50 μm.
[0013] Preferably, the particle size of CaF2 is 25-50 μm.
[0014] A method for preparing a wear-resistant self-lubricating copper-based composite material comprises the following steps:
[0015] Firstly, aluminum bronze, Ti3AlC2 and CaF2 are uniformly mixed to obtain a mixed raw material; the mixed raw material is loaded into a sintering mold, and then placed in a sintering furnace for sintering to obtain the composite material.
[0016] Preferably, the mixed raw material is obtained by ball milling under an inert gas atmosphere, wherein the ball-to-material ratio is 1:1-2:1, the ball milling speed is 150-200 r / min, and the ball milling time is 8-10 h. Further preferably, the ball milling jar and the ball milling beads are made of tungsten carbide.
[0017] Preferably, the sintering process parameters are as follows: hot pressing sintering is performed under a vacuum degree lower than 0.1 Pa, the sintering temperature is 850-900° C., the sintering pressure is 35-40 MPa, and the sintering heat and pressure holding time is 5-10 min.
[0018] Preferably, the heating rate during the sintering process is 100-150° C. / min.
[0019] Beneficial effects:
[0020] (1) The present invention provides a wear-resistant self-lubricating composite material, wherein the material generates a solid solution strengthening effect by adding Cr element to the α phase of the aluminum bronze matrix, and generates a dispersion strengthening effect by adding La2O3 to be dispersed in the aluminum bronze matrix. Compared with the existing matrix strengthening technology, the present invention combines the solid solution strengthening effect of Cr element with the dispersion strengthening effect of La2O3 by accurately controlling the relative content of Cr and La2O3, so that the material has excellent structural uniformity, hardness and strength.
[0021] (2) The present invention provides a wear-resistant self-lubricating composite material, wherein Ti3AlC2 and CaF2 are added simultaneously to produce a coupling effect, and the ratio thereof is adjusted to combine the effect of Ti3AlC2 in reducing adhesive wear with the effect of CaF2 in reducing abrasive wear, so as to reduce the friction coefficient and wear rate. The content of Ti3AlC2 and CaF2 will have a significant effect on the mechanical properties and friction properties. If Ti3AlC2 is too little and CaF2 is too much, the interface bonding force inside the aluminum bronze will decrease and the strengthening effect will not be significant, resulting in a decrease in the bending strength, compressive strength and wear resistance of the material; if Ti3AlC2 is too much and CaF2 is too little, it is difficult for the material to form a stable lubricating film at high temperature, resulting in a high friction coefficient of the material; if the total addition amount of Ti3AlC2 and CaF2 is small, it is difficult to produce a significant strengthening and lubricating effect on the entire matrix; if the total addition amount of Ti3AlC2 and CaF2 is large, the strength and wear resistance will decrease due to decreased uniformity of the structure and excessive impurities at the grain boundaries. Compared with aluminum bronze materials with added lubricating phase graphite and strengthening phase Al2O3, the present invention achieves the coupling of lubrication and wear reduction performance under high temperature conditions by accurately controlling the contents of Ti3AlC2 and CaF2, and has more excellent friction performance under high temperature conditions.
[0022] (3) The Ti3AlC2 used in the present invention is prepared from Ti powder, Al powder and graphite powder by high-energy ball milling and high-temperature sintering. Compared with the reported Ti3AlC2 preparation technology, the mass ratio of Ti powder, Al powder and graphite powder, high-energy ball milling process and high-temperature sintering process in the present invention are obtained through multiple experiments. On the one hand, the purity of Ti3AlC2 can be improved and the impurity content in the material can be reduced; on the other hand, the uniformity and surface chemical energy of Ti3AlC2 can be improved, so that it is easier to be closely combined with the aluminum bronze interface and evenly distributed during hot pressing sintering.
[0023] (4) The present invention provides a method for preparing a wear-resistant self-lubricating composite material. In the preparation method, an aluminum bronze matrix, Ti3AlC2 and CaF2 powders are ball-milled under the protection of an inert gas, the obtained mixed powder is placed in a sintering furnace for hot pressing and sintering, and the mixture is cooled in the furnace after sintering. Compared with the existing preparation technology, the preparation process of the present invention is obtained through multiple experiments. On the one hand, it can improve the uniformity and strength of the material, and on the other hand, it can improve the density and hardness of the material.
[0024] (5) The composite material of the present invention has high hardness, compressive strength and flexural strength, and low wear rate and friction coefficient, and has good anti-friction and anti-wear properties, and is suitable for use under high temperature and oil-free conditions, and can be used for friction parts under harsh working conditions such as sliding bearings, bushings, and sliders.
[0025] (6) The preparation method of the composite material of the present invention is simple, the raw materials used are environmentally friendly, the preparation cost is low, the economic benefit is high, and the application range is wide. It has broad application prospects in the fields of electricity, energy, corrosive environment and rail transportation. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.
[0027] Example 1
[0028] 70.0 g of Ti, 18.0 g of Al and 12.0 g of graphite powder were added to a ball mill made of tungsten carbide cemented carbide, and 1 mL of anhydrous ethanol and ball mill beads made of tungsten carbide cemented carbide were added according to a ball-to-material ratio of 3:1. The ball mill speed was set to 250 r / min, and the ball milling was performed under an argon protective atmosphere. The ball milling process was stopped every 10 minutes, and the ball milling was continued after stopping for 2 minutes. The ball milling was performed for 8 hours to obtain a uniformly mixed mixed powder; the mixed powder was loaded into a graphite mold, and then placed in a spark plasma sintering furnace, sintered under an argon protective atmosphere, heated to 1380°C at a heating rate of 100°C / min, kept at 1380°C for 5 minutes, and then cooled to room temperature with the furnace to obtain Ti3AlC2;
[0029] 80.0g of Cu, 6.5g of Al, 1.5g of Ni, 2.5g of Fe, 0.5g of Mn, 0.5g of Cr, 0.5g of La2O3, 3.0g of Ti3AlC2 and 5.0g of CaF2 were added into a ball mill made of tungsten carbide cemented carbide, and ball milling beads made of tungsten carbide were added according to a ball-to-material ratio of 1:1. The ball milling speed was set to 150r / min, and the ball milling was carried out under an argon protective atmosphere. During the ball milling process, the ball milling beads were rotated at intervals of 1 The milling process was repeated for 8 hours to obtain a uniformly mixed raw material. The mixed raw material was loaded into a graphite mold and then placed in a spark plasma sintering furnace for hot pressing at a vacuum degree of less than 0.1 Pa. The temperature was increased to 850°C at a heating rate of 100°C / min and a pressure of 35 MPa was applied. After maintaining the temperature and pressure at 850°C and 35 MPa for 5 minutes, the mixture was cooled to room temperature with the furnace to obtain a wear-resistant and self-lubricating copper-based composite material.
[0030] The performance test of the composite material prepared in Example 1 was carried out: the density was measured by Archimedes principle and was 7.39 g / cm 3 ; The hardness of the composite material was tested by a Vickers hardness tester and was found to be 191 HV; the mechanical properties were tested by a CMT-5205 universal material testing machine, with a compression and three-point bending displacement rate of 0.1 mm / min. The compressive strength of the composite material was measured to be 1023 MPa and the average flexural strength was 833 MPa.
[0031] The tribological properties of the composite material prepared in Example 1 were evaluated using a HT-1000 high temperature friction and wear tester. The dual ball was 316 stainless steel (diameter 4 mm, surface roughness 0.02), the load was 5 N, the sliding speed was 0.1 m / s, the friction radius was 5 mm, the running time was 30 min, and the test temperature was 20°C and 600°C. The test showed that the average friction coefficient of the friction material at 20°C was 0.28, and the average wear rate was 1.1×10 -4 mm 3 / N·m; the average friction coefficient at 600℃ is 0.45, and the average wear rate is 3.8×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0032] Example 2
[0033] 75.0 g of Ti, 15.0 g of Al and 10.0 g of graphite powder were added to a ball mill made of tungsten carbide hard alloy, and 2 mL of anhydrous ethanol and ball mill beads made of tungsten carbide hard alloy were added according to a ball-to-material ratio of 3.5:1. The ball mill speed was set to 300 r / min, and the ball milling was performed under an argon protective atmosphere. The ball milling was stopped every 10 minutes, and the ball milling was continued after stopping for 2 minutes. The ball milling was performed for 9.0 hours to obtain a uniformly mixed mixed powder; the mixed powder was loaded into a graphite mold, and then placed in a spark plasma sintering furnace, sintered under an argon protective atmosphere, heated to 1400°C at a heating rate of 130°C / min, kept at 1400°C for 10 minutes, and then cooled to room temperature with the furnace to obtain Ti3AlC2;
[0034] 68.0 g of Cu, 9.5 g of Al, 2.5 g of Ni, 2.5 g of Fe, 0.5 g of Mn, 0.5 g of Cr, 0.5 g of La2O3, 7.0 g of Ti3AlC2 and 9.0 g of CaF2 were added to a ball mill made of tungsten carbide cemented carbide, and ball milling beads made of tungsten carbide cemented carbide were added according to a ball-to-material ratio of 1.5:1. The ball milling speed was set to 180 r / min, and ball milling was carried out under an argon protective atmosphere. During the ball milling process, the tungsten carbide cemented carbide was added every 1 The milling process was stopped once every 3 minutes, and ball milling was continued after stopping for 2 minutes for 9 hours to obtain a uniformly mixed raw material. The mixed raw material was loaded into a graphite mold, and then placed in a spark plasma sintering furnace, and hot-pressed sintered at a vacuum degree of less than 0.1 Pa. The temperature was increased to 870°C at a heating rate of 120°C / min, and a pressure of 38 MPa was applied. After maintaining the temperature and pressure at 870°C and 38 MPa for 8 minutes, the mixture was cooled to room temperature with the furnace to obtain a wear-resistant and self-lubricating copper-based composite material.
[0035] The performance test of the composite material prepared in Example 2 was carried out: the density was measured by Archimedes principle and was 7.37 g / cm 3 ; The average hardness of the composite material was tested by a Vickers hardness tester and was found to be 196 HV; the mechanical properties were tested by a CMT-5205 universal material testing machine, with a compression and three-point bending displacement rate of 0.1 mm / min. The average compressive strength of the composite material was measured to be 997 MPa and the average flexural strength was 808 MPa.
[0036] The tribological properties of the composite material prepared in Example 2 were evaluated using a HT-1000 high temperature friction and wear tester. The dual ball was 316 stainless steel (diameter 4 mm, surface roughness 0.02), the load was 5 N, the sliding speed was 0.2 m / s, the friction radius was 5 mm, the running time was 30 min, and the test temperature was 20°C and 600°C. The test showed that the average friction coefficient of the friction material at 20°C was 0.23, and the average wear rate was 0.9×10-4 mm 3 / N·m; the average friction coefficient at 600℃ is 0.40, and the average wear rate is 3.1×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0037] Example 3
[0038] 71.0 g of Ti, 15.0 g of Al and 14.0 g of graphite powder were added to a ball mill made of tungsten carbide hard alloy, and 3 mL of anhydrous ethanol and ball mill beads made of tungsten carbide hard alloy were added according to a ball-to-material ratio of 4:1. The ball mill speed was set to 350 r / min, and the ball milling was performed under an argon protective atmosphere. The ball milling was stopped every 5 minutes, and the ball milling was continued after stopping for 3 minutes. The ball milling was performed for 10 hours to obtain a uniformly mixed mixed powder; the mixed powder was loaded into a graphite mold, and then placed in a spark plasma sintering furnace, sintered under an argon protective atmosphere, heated to 1420°C at a heating rate of 150°C / min, kept at 1420°C for 20 minutes, and then cooled to room temperature with the furnace to obtain Ti3AlC2;
[0039] 60.0 g of Cu, 8.5 g of Al, 2.5 g of Ni, 4.0 g of Fe, 1.0 g of Mn, 1.0 g of Cr, 1.0 g of La2O3, 10.0 g of Ti3AlC2 and 12.0 g of CaF2 were added to a ball mill made of tungsten carbide cemented carbide, and ball milling beads made of tungsten carbide were added according to a ball-to-material ratio of 2:1. The ball milling speed was set to 200 r / min, and the ball milling was carried out under an argon protective atmosphere. During the ball milling process, the ball milling beads were added at a ratio of 2:1. The milling process was repeated for 3 minutes and then continued for 10 hours to obtain a uniformly mixed raw material. The mixed raw material was loaded into a graphite mold and then placed in a spark plasma sintering furnace for hot pressing at a vacuum degree of less than 0.1 Pa. The temperature was increased to 900°C at a heating rate of 150°C / min and a pressure of 40MPa was applied. After maintaining the temperature and pressure at 900°C and 40MPa for 10 minutes, the mixture was cooled to room temperature with the furnace to obtain a wear-resistant and self-lubricating copper-based composite material.
[0040] The composite material prepared in Example 3 was tested for performance: its density was measured by Archimedes principle and was 7.35 g / cm 3 ; The average hardness of the composite material was tested by a Vickers hardness tester and was found to be 202 HV; the mechanical properties were tested by a CMT-5205 universal material testing machine, with a compression and three-point bending displacement rate of 0.1 mm / min. The average compressive strength of the composite material was measured to be 950 MPa and the average flexural strength was 766 MPa.
[0041] The high temperature tribological properties of the composite material prepared in Example 3 were evaluated using a HT-1000 high temperature friction and wear tester. The dual ball was 316 stainless steel (diameter 4 mm, surface roughness 0.02), the load was 5 N, the sliding speed was 0.2 m / s, the friction radius was 5 mm, the running time was 30 min, and the test temperature was 20°C and 600°C. The test showed that the average friction coefficient of the friction material at 20°C was 0.20, and the average wear rate was 0.7×10 -4 mm 3 / N·m; the average friction coefficient at 600℃ is 0.34, and the average wear rate is 2.6×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0042] Comparative Example 1
[0043] Compared with Example 1, Cr and La2O3 are not added in Comparative Example 1, and the specific composition ratio of the material is: 81.0g of Cu, 6.5g of Al, 1.5g of Ni, 2.5g of Fe, 0.5g of Mn, 3.0g of Ti3AlC2 and 5.0g of CaF2. The other preparation processes and process parameters are consistent with those of Example 1. The material properties obtained in Comparative Example 1 are compared with those in Example 1 (Table 1). The results show that the hardness, compressive strength and flexural strength of Comparative Example 1 decrease, and the wear rate increases. This is because when Cr and La2O3 are missing, the refinement and dispersion strengthening effects cannot be produced, the hardness and strength of the aluminum bronze matrix decrease, and then the wear resistance decreases.
[0044] Table 1 Comparison of Comparative Example 1 with Example 1
[0045]
[0046] Comparative Example 2
[0047] Compared with Example 2, Comparative Example 2 replaces the strengthening phase Ti3AlC2 with the commonly used strengthening phase Al2O3, and the mass is the same as 7.0g. Other material components, contents, and preparation processes are consistent with those of Example 2. Comparing the material properties obtained in Comparative Example 2 with those in Example 2 (Table 2), the results show that the compressive strength and flexural strength of Comparative Example 2 decrease, and the wear rate increases. This is because the interface bonding force between Al2O3 and aluminum bronze is lower than the interface bonding force between Ti3AlC2 and aluminum bronze, resulting in a decrease in material strength, and the material is more likely to peel off from the surface during friction, so the wear resistance is reduced.
[0048] Table 2 Comparison of Comparative Example 2 with Example 2
[0049]
[0050] Comparative Example 3
[0051] Compared with Example 3, Comparative Example 3 replaces the lubricating phase CaF2 with a common lubricating phase graphite, and the mass is the same as 12.0g. The other material components, contents, and preparation processes are consistent with those of Example 3. The material properties obtained in Comparative Example 3 are compared with those in Example 3 (Table 3). The results show that the friction coefficient of Comparative Example 3 increases and the wear rate increases at 600°C. This is because CaF2 has excellent lubrication properties in a high temperature environment, while the lubrication ability of graphite in a high temperature environment is not as good as that of CaF2, resulting in an increase in the friction coefficient and aggravated wear of Comparative Example 3.
[0052] Table 3 Comparison of Comparative Example 3 with Example 3
[0053]
[0054] Comparative Example 4
[0055] Compared with Example 2, Comparative Example 4 reduces the Cu content (below the specified range), increases the content of other elements (above the specified range), increases the content of the strengthening phase Ti3AlC2 (above the specified range), and reduces the content of the lubricating phase CaF2 (below the specified range) in the aluminum bronze matrix. The specific composition ratio is: 57.0g of Cu, 13.0g of Al, 4.0g of Ni, 5.0g of Fe, 2.0g of Mn, 2.0g of Cr, 2.0g of La2O3, 13.0g of Ti3AlC2 and 2.0g of CaF2. Other preparation processes and process parameters are consistent with those of Example 2. The material properties obtained in Comparative Example 4 are compared with those in Example 2 (Table 4). The results show that the compressive strength and flexural strength of Comparative Example 4 decrease, and the friction coefficient and wear rate increase. The main reasons are as follows: reducing the Cu content and increasing the content of other alloying elements in the aluminum bronze matrix causes the phase composition of the alloy to change, the impurity elements to increase, and the internal interface bonding force of the material to decrease, so the compressive strength and flexural strength decrease, and the wear rate increases; too much strengthening phase Ti3AlC2 and too little lubricating phase CaF2 make it difficult for the material to form a stable lubricating film on the surface during friction and wear, so the friction coefficient and wear rate increase.
[0056] Table 4 Comparison of Comparative Example 4 with Example 2
[0057]
[0058] Comparative Example 5
[0059] Relative to Example 3, high-energy ball milling was not performed when preparing Ti3AlC2 powder, and the sintering temperature was lower than the specified range. The specific preparation process of Ti3AlC2 powder is as follows: 71.0g of Ti, 15.0g of Al and 14.0g of graphite powder are added to a ball mill made of tungsten carbide cemented carbide, and grinding balls made of tungsten carbide cemented carbide are added according to a ball-to-material ratio of 1:1, and the ball milling speed is set to 150r / min, and the ball milling is performed for 5h under an argon protective atmosphere; the mixed powder is loaded into a graphite mold, and then placed in a discharge plasma sintering furnace, sintered under an argon protective atmosphere, heated to 1200°C at a heating rate of 150°C / min, and kept at 1200°C for 20min, and then cooled to room temperature with the furnace. Other material components, contents, and preparation processes are consistent with those in Example 3. The material properties obtained in Comparative Example 5 are compared with those in Example 3 (Table 5). The results show that the strength of the material obtained in Comparative Example 5 decreases and the wear rate increases. This is because in Comparative Example 5, high-energy ball milling was not performed when preparing Ti3AlC2 powder and the sintering temperature was low, resulting in uneven composition of the Ti3AlC2 powder and low surface chemical energy, and the bonding strength with the matrix decreased after being added to the aluminum bronze matrix.
[0060] Table 5 Comparison of Comparative Example 5 with Example 3
[0061]
[0062] Comparative Example 6
[0063] Relative to Example 1, when hot pressing and sintering are performed to prepare the composite material in Comparative Example 6, the sintering temperature is higher than the specified range, and the sintering pressure is lower than the specified range. The specific sintering process is as follows: the mixed raw material is loaded into a graphite mold, and then placed in a discharge plasma sintering furnace, and hot pressing and sintering is performed at a vacuum degree lower than 0.1 Pa, and the temperature is increased to 950°C at a heating rate of 100°C / min, and a pressure of 30MPa is applied. After keeping the temperature and pressure at 950°C and 30MPa for 5 minutes, the material is cooled to room temperature with the furnace to obtain a wear-resistant self-lubricating copper-based composite material. The other material components, contents, and preparation processes are consistent with those in Example 1. The material properties obtained in Comparative Example 6 are compared with those in Example 1 (Table 6). The results show that the hardness and strength of the material obtained in Comparative Example 6 decrease, and the wear rate increases. This is because the sintering temperature of Comparative Example 6 is too high, resulting in component segregation of aluminum bronze, and the α phase and κ phase formed by Cu and Al are uneven. At the same time, the sintering pressure of Comparative Example 6 is too low, resulting in a decrease in the hardness and strength of the material.
[0064] Table 6 Comparison of Comparative Example 6 with Example 1
[0065]
[0066] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A wear-resistant self-lubricating copper-based composite material, characterized in that: Taking the total mass of the raw materials for preparing the composite material as 100%, the composition of the raw materials and the mass percentage of each component are as follows: 78-92% of aluminum bronze, 3-10% of Ti3AlC2 and 5-12% of CaF2; The components of the aluminum bronze and the mass percentage of each component in the raw material for preparing the composite material are as follows: Cu 60-80%, Al 6.5-9.5%, Ni 1.5-2.5%, Fe 2.5-4%, Mn 0.5-1%, Cr 0.5-1%, and La2O3 0.5-1.0%.
2. The wear-resistant self-lubricating copper-based composite material according to claim 1, characterized in that: The Ti3AlC2 is prepared by sintering a mixed powder of Ti powder, Al powder and graphite powder under an inert gas protective atmosphere, wherein the sintering temperature is 1380-1420° C. and the sintering holding time is 5-20 min.
3. The wear-resistant self-lubricating copper-based composite material according to claim 2, characterized in that: Ti powder, Al powder and graphite powder are mixed by high-energy ball milling under an inert gas protective atmosphere, wherein the ball-to-material ratio is 3:1-4:1, the ball milling speed is 250-350r / min, the ball milling time is 8-10h, anhydrous ethanol is added before ball milling, the ball milling process is stopped every 5-10min, and the ball milling is continued after stopping for 2-3min.
4. A wear-resistant self-lubricating copper-based composite material according to claim 2 or 3, characterized in that: Taking the total mass of raw materials for preparing Ti3AlC2 as 100%, the composition of the raw materials and the mass percentage of each component are as follows: Ti powder 70-75%, Al powder 15-18%, and graphite powder 9-14%.
5. The wear-resistant self-lubricating copper-based composite material according to claim 2 or 3, characterized in that: The particle sizes of Ti powder, Al powder and graphite powder are 25-50 μm; the particle size of the prepared Ti3AlC2 is 25-50 μm.
6. The wear-resistant self-lubricating copper-based composite material according to claim 1, characterized in that: The particle size of the single substance powders of Cu, Al, Ni, Fe, Mn and Cr is 200-300 mesh, and the particle size of La2O3 is 25-50 μm.
7. A method for preparing the wear-resistant self-lubricating copper-based composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Firstly, aluminum bronze, Ti3AlC2 and CaF2 are uniformly mixed to obtain a mixed raw material; the mixed raw material is loaded into a sintering mold, and then placed in a sintering furnace for sintering to obtain the composite material.
8. The method for preparing the wear-resistant self-lubricating copper-based composite material according to claim 7, characterized in that: Under an inert gas protective atmosphere, a ball milling mixing method is used to obtain a mixed raw material, wherein the ball-to-material ratio is 1:1-2:1, the ball milling speed is 150-200 r / min, and the ball milling time is 8-10 h.
9. The method for preparing the wear-resistant self-lubricating copper-based composite material according to claim 7, characterized in that: The sintering process parameters are as follows: hot pressing sintering is carried out under a vacuum degree lower than 0.1 Pa, the sintering temperature is 850-900° C., the sintering pressure is 35-40 MPa, and the sintering heat preservation and pressure holding time is 5-10 min.
Citation Information
Patent Citations
Self-lubricating copper-Ti3SiC2-NbSe2 composite material and preparation method thereof
CN102703161A
Brake block friction material taking Mn+1XAn lamellar compound as antifriction phase and preparation method
CN103184385A
High-strength antifriction and wearable aluminum-manganese bronze alloy
CN104388749A
Copper-aluminum-iron-nickel-manganese-chromium-silicon alloy capable of improving wear-resistant performance
CN105088004A
Copper-based high-temperature self-lubricating composite material
CN107586989A